National Character Education in the Midst of Social Dynamics of Indonesian Learners - Aminah, Siti; Mulyasari, Nur Rokhmah Dwi; Khasnah, Isnaeni Asifatul (Proceedings Series on Social Sciences & Humanities, 2025)
Character education is an essential component in shaping students who are not only intellectually intelligent, but also morally and socially resilient. In the midst of increasingly complex social dynamics-including globalization, information technology development, and shifting cultural values-character education in Indonesia faces significant challenges. This article examines the strategic role of character education in shaping the nation's generation with integrity and adaptive to social change. Using the literature study method by referring to the latest scientific literature, this study found that the success of Character Education character education is influenced by the social conditions of students, family parenting, school culture, and digital media. It also emphasizes the importance of designing character education that is contextual and relevant to social Indonesian Learners realities in various regions. A collaborative approach between schools, families and communities is key in creating an educational environment that supports character strengthening. Thus, the national education system needs to continuously adapt so that character education strategies remain relevant and effective amid dynamic social changes.